2017
DOI: 10.1021/acs.joc.6b02732
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical Properties of Phenacylphenantridine Difluoroboranyls: Effect of Substituent and Double Benzannulation

Abstract: In this study we present a new series of phenantridine-based substituted difluoroboranyls. The effects of substitution and double benzannulation on their photophysical properties were examined with experimental techniques and compared with the results obtained for previously reported quinoline and isoquinoline derivatives. The experimental characterizations are supported by state-of-the-art quantum-chemical calculations. In particular, the theoretical calculations were performed to gain insights into the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 89 publications
(124 reference statements)
1
34
0
Order By: Relevance
“…Fluorescent difluoroborates are a broad class of compounds that find applications in many different areas, of which fluorescent molecular probes (Cantu ¨rk et al, 2015;Gabe et al, 2006) and dyes for biolabelling (Niu et al, 2012;Roubinet et al, 2015) are the most important. Studies focused on rational modifications of their properties indicated the importance of methods based on substituent exchange (Os ´miałowski et al, 2015;Zakrzewska et al, 2013a,b), benzannulation (Grabarz et al, 2017) or the replacement of single atoms within a molecule (Je ˛drzejewska et al, 2016;Dı ´az-Moscoso et al, 2014). In BF 2related compounds, the last named modification can be realized by two general approaches, namely, changing the atom interacting with boron (Je ˛drzejewska et al, 2016) or changing the atoms that are in close proximity to the BF 2 group (as in, for example, aza-BODIPY versus BODIPY dyes) (Yoshii et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescent difluoroborates are a broad class of compounds that find applications in many different areas, of which fluorescent molecular probes (Cantu ¨rk et al, 2015;Gabe et al, 2006) and dyes for biolabelling (Niu et al, 2012;Roubinet et al, 2015) are the most important. Studies focused on rational modifications of their properties indicated the importance of methods based on substituent exchange (Os ´miałowski et al, 2015;Zakrzewska et al, 2013a,b), benzannulation (Grabarz et al, 2017) or the replacement of single atoms within a molecule (Je ˛drzejewska et al, 2016;Dı ´az-Moscoso et al, 2014). In BF 2related compounds, the last named modification can be realized by two general approaches, namely, changing the atom interacting with boron (Je ˛drzejewska et al, 2016) or changing the atoms that are in close proximity to the BF 2 group (as in, for example, aza-BODIPY versus BODIPY dyes) (Yoshii et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32] However, the main challengesw ith the BODIPY dyes are the tedious synthesis, low reaction yields, and weak solid-state luminescence due to very tight packing combined with as mall Stokes shift, which leads to self-quenching through energy transfer. [33,34] To overcome these limitations of BODIPYsa nd to meet the demand for new emissivem aterials, new families of tetracoordinate boron compounds with N-B-C, [35][36][37][38][39] N-B-O, [28,[40][41][42][43][44][45] and O-B-O [46][47][48] connectivity have been investigated.R ecently,f ascinating opticalf eatures such as dual, [31] tricolor, [32] and white-light emission [49] and self-calibrating ratiometric anion sensing [50] were realized with TAB-appendedB ODIPY compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In this pursuit, Le Bahers, Adamo, and Ciofini [5] pioneered a quantitative analysis that has been useful in the analysis of light-absorbing organic chromophores. [6] In their approach the charge transferred (q CT ) in a photochemical transition is calculated from the sum of all per-atom differences in partial atomic charges (PAC) having the same sign. The associated vector d CT , across which charge is transferred, is computed between the geometric barycenters of the positive and negative PAC difference.…”
Section: Introductionmentioning
confidence: 99%
“…In this pursuit, Le Bahers, Adamo, and Ciofini pioneered a quantitative analysis that has been useful in the analysis of light‐absorbing organic chromophores . In their approach the charge transferred ( q CT ) in a photochemical transition is calculated from the sum of all per‐atom differences in partial atomic charges (PAC) having the same sign.…”
Section: Introductionmentioning
confidence: 99%